2008
DOI: 10.1111/j.1751-9004.2008.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

The Self in Procedural Fairness

Abstract: Procedural fairness (whether the organizational decision-making process is perceived as fair) has profound psychological effects on organizational members. A vital reason for these effects is that organizational procedures communicate information which is relevant to the self. Specifically, this information is relevant to different types of self (individual, collective, relational) and, more importantly, to different motives within each type of self. As such, procedures satisfy the motives of uncertainty reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 71 publications
1
26
0
1
Order By: Relevance
“…It has mainly been considered as a theory of intragroup process, and has been studied most often in terms of how the group affect the individual. Indeed, decision‐making situations studied in the relational model involve a specific target person who is being treated (un)fairly as an individual, and because of this his or her treatment has only relevance for this individual in terms of his or her interpersonal relationships, or in other words, the treatment primarily impacts the relational self (Sedikides & Brewer, 2001; Sedikides, Hart, & De Cremer, 2008). For instance, an employee can be treated procedurally fair or unfair and this affects his or her perceptions and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It has mainly been considered as a theory of intragroup process, and has been studied most often in terms of how the group affect the individual. Indeed, decision‐making situations studied in the relational model involve a specific target person who is being treated (un)fairly as an individual, and because of this his or her treatment has only relevance for this individual in terms of his or her interpersonal relationships, or in other words, the treatment primarily impacts the relational self (Sedikides & Brewer, 2001; Sedikides, Hart, & De Cremer, 2008). For instance, an employee can be treated procedurally fair or unfair and this affects his or her perceptions and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that individuals with uncertain identities are particularly sensitive to variations in procedural justice (De Cremer & Sedikides, 2005; see also Sedikides et al, 2008). In one study, participants who felt more uncertain about whether they belonged in a group showed an increase in affiliation or identification in response to being granted voice and fair procedures (De Cremer, Van Knippenberg, Van Dijke, & Bos, 2004).…”
Section: A Identity Uncertainty and Malleabilitymentioning
confidence: 99%
“…An authority figure treating an adolescent with respect can thus signal to that young person that the group as a whole values them, heightening their feelings of identification with that group as well as their sense of self‐esteem (Tyler, Degoey, & Smith, ). Procedural fairness can affect all aspects of self, including the individual, relational, and collective by reducing uncertainty, providing self‐enhancement, affirming status, and conveying belonging (Sedikides, Hart, & De Cremer, ). Conversely, the absence of fairness or the experience of unfair, aversive treatment by any authority figure may be similarly or even more informative.…”
Section: Part 2: Reconceptualizing Adolescent Cognitionmentioning
confidence: 99%
“…It is the accuracy in procedures in company's decisions [12]. Lambert in this work describes impartiality as an important component of organizational environment and employment.…”
Section: Perceived Procedural Justicementioning
confidence: 99%